2017
DOI: 10.7213/academica.15.s02.2017.a05
|View full text |Cite
|
Sign up to set email alerts
|

Plantas tóxicas de interesse pecuário na região Centro-Oeste do Brasil

Abstract: align="left">Diversas plantas são conhecidas por causar intoxicação em animais de produção no Centro-Oeste do Brasil. Nesta revisão nós discutimos os aspectos epidemiológicos, patogenia, sinais clínicos, achados patológicos, medidas de controle e tratamento das principais plantas que causam intoxicações.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Among the toxic plants that grow in the Brazilian Central-West region and that can cause liver, kidney, and digestive tract lesions in cattle (Lemos & Lima 2017), it is necessary to consider poisoning by S. fissuratum E.M.O Martins as a differential diagnosis. The clinical-pathological condition observed in cattle poisoned by S. fissuratum (Ferreira et al 2009) is partially similar to that observed in this study; however, it presents with severely intense findings that are compatible with those of renal and hepatic insufficiency and photosensitization cases (Lazaro et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Among the toxic plants that grow in the Brazilian Central-West region and that can cause liver, kidney, and digestive tract lesions in cattle (Lemos & Lima 2017), it is necessary to consider poisoning by S. fissuratum E.M.O Martins as a differential diagnosis. The clinical-pathological condition observed in cattle poisoned by S. fissuratum (Ferreira et al 2009) is partially similar to that observed in this study; however, it presents with severely intense findings that are compatible with those of renal and hepatic insufficiency and photosensitization cases (Lazaro et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Plantas tóxicas são importantes causas de prejuízos econômicos em animais de produção em diversas regiões do Brasil (SANT 'ANA et al, 2014;LEMOS;. Dentre as enfermidades causadas por plantas tóxicas destaca-se a calcinose enzoótica, doença que ocorre mundialmente e que é associada à ingestão de plantas calcinogênicas (SANTOS et al, 2011).…”
Section: Introductionunclassified